Design of Rule Based Algorithm Based on IoT (Internet of Things) and Water Level Sensor to Monitor the Tide of Bengawan Solo - zu fahim, wahyu; Handoyo, Eko; Shodiq, Muhammad (Universitas Muhammadiyah Lamongan, 2024)
Laren Village in Laren District, Lamongan Regency, is traversed by the Bengawan Solo River, which is crucial for agriculture, fisheries, industry, and domestic needs. However, excessive use poses risks of pollution and flooding. Floods can cause material losses, infrastructure damage, environmental contamination, disease outbreaks, traffic disruption, and water scarcity. Effective mitigation measures are vital to reduce these risks. Internet of Things (IoT)-based technology offers an effective solution for flood risk mitigation. IoT enables real-time monitoring and decision-making using rule-based algorithms that analyze data patterns, set conditions, and automatically respond to potential threats. On August 6, 2024, observation data showed Bengawan Solo's water level ranged between 119 cm and 170 cm, mostly categorized as